(2+1 ') mass analyzed threshold ionization (MATI) spectroscopy of the CD3 radical - Dickinson, H; Chelmick, T; Softley, T (2001)
The mass analyzed threshold ionization (MATI) spectrum of CD3, recorded using two-colour (2+1′) multiphoton excitation via the Q-branch transition to the 3pz Rydberg state, is reported. The fast CD3 radicals are produced by photodissociation of CD3I at 280 nm. The spectroscopy provides a possible route to state-selection of rovibronic levels of the CD3+ ion, or for Rydberg tagging of the CD3 fragments in a photodissociation experiment. The MATI spectrum is simulated using a simple Hund's case (b) to Hund's case (d) intensity model. The variable parameters optimized in the model are the ratio of radial transition moments to the s and d channels (1:1), the MATI bandwidth (~15 cm-1) and asymmetric lineshape (determined by the discrimination field and the high-n Rydberg decay), and the ionization potential of CD3(79287±5cm-1). © 2001 Elsevier Science B.V.